2020
DOI: 10.1016/j.rdc.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Systemic Lupus Erythematosus

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 110 publications
(176 reference statements)
2
32
0
Order By: Relevance
“…A previous study showed that systemic lupus erythematosus is highly associated with increased cancer risk compared with the general population ( Song et al, 2018 ). The underlying pathophysiologic mechanisms are still not fully understood, but possible factors include lupus-related medications, inherent immune system abnormalities, viral infections, and/or traditional cancer risk factors ( Ladouceur et al, 2020 ). Other pathways which significantly enriched in a high-risk cohort include the RIG l (retinoic acid inducible-gene 1)-like receptor signaling pathway, the NOD (nucleotide-binding oligomerization domain)-like receptor signaling pathway, the cytoplasmic DNA sensing pathway, antigen processing and presentation, primary immunodeficiency, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that systemic lupus erythematosus is highly associated with increased cancer risk compared with the general population ( Song et al, 2018 ). The underlying pathophysiologic mechanisms are still not fully understood, but possible factors include lupus-related medications, inherent immune system abnormalities, viral infections, and/or traditional cancer risk factors ( Ladouceur et al, 2020 ). Other pathways which significantly enriched in a high-risk cohort include the RIG l (retinoic acid inducible-gene 1)-like receptor signaling pathway, the NOD (nucleotide-binding oligomerization domain)-like receptor signaling pathway, the cytoplasmic DNA sensing pathway, antigen processing and presentation, primary immunodeficiency, etc.…”
Section: Discussionmentioning
confidence: 99%
“…As SLE increases the risk of NHL by fourfold ( 2 ), it seems tempting to speculate that the DLBCL arose secondary to the chronic inflammatory disease. Indeed, the presented case suggests a possible link between autoimmune reactive diseases as an underlying chronic inflammatory trigger factor for NHL, a phenomenon that is particularly known in extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue lymphomas ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diffused large B-cell lymphoma (DLBCL) is a highly heterogeneous disease and represents the most common subtype of non-Hodgkin’s lymphoma (NHL) in adult patients ( 1 ). Systemic lupus erythematosus (SLE) increases the risk of NHL by fourfold mainly attributed to the chronic inflammatory state, dysregulation of cytokines, and higher expression of a proliferation-inducing ligand ( 2 ). The main connecting feature of both diseases is that the B cells are at the center of the respective pathophysiological changes.…”
Section: Introductionmentioning
confidence: 99%
“…While SLE is associated with a 4-fold increased risk of non-Hodgkin lymphoma, some studies report a decreased risk of female hormone-dependent cancers: breast, ovarian and endometrial [20][21][22]. Several studies also reported increased risk of cervical, vulva/vaginal, head and neck, thyroid, bladder and kidney, liver and nonmelanoma skin cancer in patients with SLE [20,21,[23][24][25][26][27]. The risk of malignancy in scleroderma has been described in three meta-analyses [28][29][30][31].…”
Section: Coexistence Of Rheumatic Diseases and Cancermentioning
confidence: 99%